Hubungan antara Komitmen Organisasi dengan Kesiapan untuk Berubah pada Karyawan Ramayana Plaza Andalas Padang - Adinda Havizah; Free Dirga Dwatra (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aims to determine the relationship between organizational commitment and readiness for change among employees at Ramayana Plaza Andalas Padang. The background of this study emphasizes the importance of human resource readiness in facing the increasingly rapid dynamics of organizational change, whether due to globalization, technological developments, or increasingly competitive market competition. Organizational change demands active involvement and psychological readiness from employees, and one factor believed to play a significant role in this readiness is the level of commitment to the organization. This study used a quantitative approach with a nonprobability sampling method, where data were collected through a questionnaire using a Likert scale. Respondents were employees from various departments at Ramayana Plaza Andalas Padang. The results showed a significant relationship between organizational commitment and readiness for change. Specifically, affective commitment—which is an employee's emotional cessation of feelings toward the organization—and continuance commitment, which relates to the perception of the costs of leaving the organization, showed a positive relationship with readiness for change. Conversely, normative commitment, which stems from a sense of moral obligation to remain employed, showed a negative correlation, indicating that moral pressure without emotional involvement can hinder readiness for change. These findings indicate that although the overall level of readiness is quite high, several aspects such as fit (the appropriateness of change), change efficacy (belief in the ability to change), and management support still need improvement. Therefore, it is recommended that organizations focus more on strengthening affective commitment by actively involving employees in the decision-making process, building open communication, and providing training and coaching that supports ongoing readiness for change. Thus, the success of organizational change is greatly influenced by the quality of the emotional connection between employees and the organization.